2019
DOI: 10.1093/ofid/ofy169
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Day Incubation Period of Plasmodium falciparum Infection in a Nonimmune Patient in Ghana: A Case Report

Abstract: Plasmodium falciparum can cause severe infection and has the shortest incubation period compared with all the other Plasmodium species. Incubation periods of 9–14 days for the immune and 6–14 days for the nonimmune have been reported for P. falciparum. However, an incubation period of less than 5 days has not been reported, as of yet. This report presents a case of a 23-year-old nonimmune female who presented with signs and symptoms 4 days after being bitten by mosquitoes while visiting Ghana. The patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…Malaria is a mosquito-transmitted infection that affects 219 million people and causes 435 thousand deaths worldwide [ 1 ]. Among the 5 Plasmodium species causing malaria in humans, Plasmodium falciparum is responsible for the most severe forms of malaria [ 2 ]. In Vietnam, P. falciparum is the most prevalent malaria parasite followed by Plasmodium vivax [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is a mosquito-transmitted infection that affects 219 million people and causes 435 thousand deaths worldwide [ 1 ]. Among the 5 Plasmodium species causing malaria in humans, Plasmodium falciparum is responsible for the most severe forms of malaria [ 2 ]. In Vietnam, P. falciparum is the most prevalent malaria parasite followed by Plasmodium vivax [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This results in a faster and increased rate of malaria parasite transmission from an infected person to a healthy individual. The incubation period (intrinsic) within the body of the newly infected individual can also vary and may be as short as four days [ 50 ]. Our data suggest that malaria incidence declined at a temperature below 15.6 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria cases diagnosed within 7 days from the start of a trip were not included in the analysis because the incubation period of Plasmodium falciparum malaria typically ranges from 7 to 14 days depending on the immune status of the individual. [25][26][27] Characteristics of study participants and individual trips were reported as proportions for categorical variables and medians with interquartile ranges for continuous variables.…”
Section: Methodsmentioning
confidence: 99%